“In the First Place, We Don’t Like to Be Called ‘Refugees’”: Dilemmas of Representation and Transversal Politics in the Participatory Art Project 100% FOREIGN? - Anne Ring Petersen (Humanities, 2021)
100% FOREIGN? (100% FREMMED?) is an art project consisting of 250 life stories of individuals who were granted asylum in Denmark between 1956 and 2019. Thus, it can be said to form a collective portrait that inserts citizens of refugee backgrounds into the narrative of the nation, thereby expanding the idea of national identity and culture. 100% FOREIGN? allows us to think of participatory art as a privileged site for the exploration of intersubjective relations and the question of how to “represent” citizens with refugee experience as well as the history and practice of asylum. The conflicting aims and perceptions involved in such representations are many, as suggested by the opening sentence of Hannah Arendt’s 1943 essay “We, Refugees”: “In the first place, we don’t like to be called ‘refugees’”. Using 100% FOREIGN? as an analytical reference point, this article discusses some of the ethical and political implications of representing former refugees. It briefly considers recent Danish immigration and asylum policies to situate the project in its regional European context and argues that, similarly to its neighbouring countries, Denmark can be described as a “postmigrant society” (Foroutan). To frame 100% FOREIGN? theoretically, this article draws on Arendt’s essay, Trinh T. Minh-ha’s concept of speaking nearby, as well as the feminist concept of transversal politics (Meskimmon, Yuval-Davis). It is hoped that this approach will lead to a deeper understanding of what participatory art can bring to the ethical politics of representing refugee experience.